2014
DOI: 10.1016/j.jconrel.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the cold-chain dependence of a nanoemulsion adjuvanted vaccine against tuberculosis by lyophilization

Abstract: Next-generation rationally-designed vaccine adjuvants represent a significant breakthrough to enable development of vaccines against challenging diseases including tuberculosis, HIV, and malaria. New vaccine candidates often require maintenance of a cold-chain process to ensure long-term stability and separate vials to enable bedside mixing of antigen and adjuvant. This presents a significant financial and technological barrier to worldwide implementation of such vaccines. Herein we describe the development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…The six selected formulations were subsequently tested in an accelerated physicochemical stability study, and three formulations were identified that met our predefined stability criteria and demonstrated greater stability against GLA degradation and particle size increase than the previously described formulation. 24 The identified formulations contained the following excipients: trehalose-Tris, trehalosephosphate, and sucrose-phosphate. These formulations remained immunogenic (ie, inducing robust IgG2c antibodies and CD4+ TH1 cells) after lyophilization and heat stress for up to 3 months at temperatures up to 50°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The six selected formulations were subsequently tested in an accelerated physicochemical stability study, and three formulations were identified that met our predefined stability criteria and demonstrated greater stability against GLA degradation and particle size increase than the previously described formulation. 24 The identified formulations contained the following excipients: trehalose-Tris, trehalosephosphate, and sucrose-phosphate. These formulations remained immunogenic (ie, inducing robust IgG2c antibodies and CD4+ TH1 cells) after lyophilization and heat stress for up to 3 months at temperatures up to 50°C.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown to convey partial stability to ID93 + GLA-SE after storage at elevated temperatures. 24 The goal of this study was to identify one or more formulations that convey stability after 3 months storage at 37°C as demonstrated by the following preset criteria: retention of greater than 80% of the chemical components (ID93 and GLA), and less than a 50% increase in particle size upon reconstitution. Data were collected during this study at five storage temperatures (−20, 2-8, 25, 37, and 50°C), and Figure 11 summarizes the data after 3 months storage.…”
Section: Stability Of Lead Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TLR8As such as the imidazoquinoline R848 (TLR7/8A), can induce adult-like Th cytokine induction and co-stimulatory molecule expression in neonatal leukocytes suggesting they may be promising candidate neonatal vaccine adjuvants (18, 2426). For novel adjuvants, a practical approach to characterize adjuvant-induced responses employs in vitro human cell systems that model the immune response (21, 2628), and may inform subsequent adjuvant selection for in vivo studies.…”
mentioning
confidence: 99%
“…GLA‐stable emulsion (GLA‐SE), a TLR4 agonist formulated in a stable nano‐emulsion of squalene oil, induces a strong T‐helper 1 (T H 1) response in mice when formulated with the clinically tested TB vaccine polyprotein fusion antigen designated as ID93 . Since diminished T‐cell memory responses have been shown with B‐cell deficits in several models of infection we asked whether B cells were necessary for the induction of T H 1 responses to this vaccine.…”
Section: Resultsmentioning
confidence: 99%